2016
DOI: 10.1038/npjamd.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Metformin decreases progerin expression and alleviates pathological defects of Hutchinson–Gilford progeria syndrome cells

Abstract: Hutchinson–Gilford progeria syndrome (HGPS) is a rare genetic disorder that causes systemic accelerated aging in children. This syndrome is due to a mutation in the LMNA gene that leads to the production of a truncated and toxic form of lamin A called progerin. Because the balance between the A-type lamins is controlled by the RNA-binding protein SRSF1, we have hypothesized that its inhibition may have therapeutic effects for HGPS. For this purpose, we evaluated the antidiabetic drug metformin and demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Despite conflicting data from different model systems, there is a trend for increases in activating histone marks (e.g., H3K4m2/3, H3K36me3) and decreases in repressive histone marks (e.g., H3K9m2/3, H3K27me3) indicative of a more actively transcribed genome, which is consistent with a well‐recognized open chromatin conformation in aging cells and organisms that culminates in the so‐called heterochromatin loss model of aging (Pal & Tyler, 2016). Metformin's ability to robustly restore the global levels of H3K27me3 in fibroblasts obtained from aged individuals or from patients with premature aging syndromes supports the notion that metformin could directly regulate the biological machinery of human aging by directly modifying aging‐associated histone mark changes and adds a new epigenetic dimension to the recent discovery of its capacity to alleviate the pathological defects of accelerated aging (Egesipe et al., 2016). Recent studies using naturally long‐lived and cancer‐resistant organisms have provided key clues to suggest that engineering more stable, H3K27me3‐enriched epigenomes might prevent cancer and extend human lifespan (Tan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite conflicting data from different model systems, there is a trend for increases in activating histone marks (e.g., H3K4m2/3, H3K36me3) and decreases in repressive histone marks (e.g., H3K9m2/3, H3K27me3) indicative of a more actively transcribed genome, which is consistent with a well‐recognized open chromatin conformation in aging cells and organisms that culminates in the so‐called heterochromatin loss model of aging (Pal & Tyler, 2016). Metformin's ability to robustly restore the global levels of H3K27me3 in fibroblasts obtained from aged individuals or from patients with premature aging syndromes supports the notion that metformin could directly regulate the biological machinery of human aging by directly modifying aging‐associated histone mark changes and adds a new epigenetic dimension to the recent discovery of its capacity to alleviate the pathological defects of accelerated aging (Egesipe et al., 2016). Recent studies using naturally long‐lived and cancer‐resistant organisms have provided key clues to suggest that engineering more stable, H3K27me3‐enriched epigenomes might prevent cancer and extend human lifespan (Tan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when HGPS dermal fibroblasts were treated with metformin, there was partial restoration of normal nuclear phenotypes, delayed senescence, decreased DNA damage, activation of AMPK phosphorylation, and decreased ROS formation, all while also suppressing progerin expression [92]. Another group also showed the benefit of metformin, though suggested this might be through decreased SRSF1 expression, which has been shown to affect alternative splicing of LMNA in humans and mice [93]. Thus, as we understand more about progeria and metformin, this is one such drug which has important metabolic effects which might gain greater importance in the coming years.…”
Section: Medianmentioning
confidence: 99%
“…HPGS is due to a mutation in the lamin A (LMNA) gene that leads to the production of a truncated and toxic form of LMNA, called progerin ( 3 ). Progerin accumulates and triggers growth impairment, lipodystrophy, dermal and bone abnormalities and cardiovascular changes, leading to a shortened lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…In a current study it has been demonstrated that metformin reduced progerin expression by regulating SRSF1 expression and altering the pathological phenotypes of HGPS cells. After treatment with 5 mmol/L of metformin, a decrease in SRSF1 protein of up to 40% could be demonstrated ( 3 ). Therefore, it may be interesting to explore the therapeutic potential of metformin in patients with this form of progeria.…”
Section: Discussionmentioning
confidence: 99%